LAMA WAKTU PENGHENTIAN KONSUMSI SOJU TERHADAP KADAR ALKOHOL HATI, MORFOLOGI HATI, DAN GAMBARAN HEMATOLOGI TIKUS PUTIH - Tiffany Angelita Putri Mileva; Ni Wayan Sudatri; I Made Sara Wijana (Program Studi Biologi Universitas Udayana, 2024)
Alcohol consumption behaviors such as soju can increase metabolic syndrome disease. The elimination of alcohol in the body can determine the last time a person consumed alcohol through post-absorption assessment of alcohol. This study was conducted to determine changes in liver macroscopic morphology, liver alcohol levels and hematological features after stopping soju administration in white rats. The research design used was a complete randomized design with 4 treatments, namely the examination time P(0) 0 days, P(1) 3 days, P(2) 7 days, and P(3) 10 days. The methods used in this study are liver weight weighing, observation of macroscopic morphological conditions of the liver, examination of alcohol levels with gas chromatography-flame ionization detector and hematological examination with haematology analyzer. The results showed that stopping soju for 10 days had a significant effect on reducing liver weight and reducing fatty liver, decreased alcohol levels, red blood cell count, PCV percentage and hemoglobin levels that returned to the normal range. While the number of white blood cells does not show any influence and the value is below the normal range. Keywords: alcohol, liver, blood profile, soju, white rat